2015
DOI: 10.1007/s00170-015-7627-8
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface damage in high-speed grinding of brittle materials considering kinematic characteristics of the grinding process

Abstract: Subsurface damage (SSD) induced during abrasive grain machining process strongly influences the mechanical strength and subsurface quality of the brittle components. Therefore, it is meaningful to study the relationship between SSD and grinding parameters. The methods of theoretical analysis, numerical simulation and experimental testing are used to analyze the SSD of brittle materials in high-speed grinding. The results of numerical simulation are consistent with those of theoretical analysis and experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 48 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…1517 Wear of the girt is re-sharpened by further process during grinding of hard materials. 18 Grinding force is an important response, which reflects the chip formation and surface integrity. 19 During the grinding process, grit makes physical contact with the workpiece and slides over the workpiece.…”
Section: Introductionmentioning
confidence: 99%
“…1517 Wear of the girt is re-sharpened by further process during grinding of hard materials. 18 Grinding force is an important response, which reflects the chip formation and surface integrity. 19 During the grinding process, grit makes physical contact with the workpiece and slides over the workpiece.…”
Section: Introductionmentioning
confidence: 99%
“…Blaineau et al obtained the relationship between SSD depth and grinding force by comparing experimental results with discrete element method simulation results [ 21 ]. Wang et al used the method of theoretical analysis, numerical simulation, and experimental testing to analyze the SSD during the high-speed grinding of brittle materials [ 22 ]. However, theoretical studies on the SSD of hard brittle materials in the polishing process have been reported with limited success, which is likely because the majority of existing studies rarely take systematic theoretical models for SSD and three-dimensional (3D) dynamic analysis into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…In HSG process, the grinding wheel linear speed could reach up to higher than 120 m/s (Pang et al, 2018), compared with conventional turning or milling of about 10 m/s or less. Under this circumstance, the machining strain rate could be higher than 10 -5 /s (Wang et al, 2016), which will definitely cause a change of materials properties. Wang et al (2016) simulated the high speed grinding induced damages and cracks in BK7 glass grinding, which concluded that the effect of grinding depth is weaker than wheel speed and a smaller abrasive grain is advantageous to subsurface quality.…”
mentioning
confidence: 99%
“…Under this circumstance, the machining strain rate could be higher than 10 -5 /s (Wang et al, 2016), which will definitely cause a change of materials properties. Wang et al (2016) simulated the high speed grinding induced damages and cracks in BK7 glass grinding, which concluded that the effect of grinding depth is weaker than wheel speed and a smaller abrasive grain is advantageous to subsurface quality. That was based on traditional finite element simulation method and the change of material properties have not been discussed in detail.…”
mentioning
confidence: 99%